Pendidikan Anak Usia Dini Dalam Islam - Nanang Abdul Jamal; Ahmad Wahyudi (LPPM Institut Al-Ma`arif Way Kanan Lampung, 2021)
ABSTRACT Children are a mandate that Allah entrusts to both parents. Children basically have to get adequate care, protection, attention and education from both parents, because the child's personality when he grows up and keshalehan in behavior is very dependent on his childhood education, especially education obtained from parents or family and the environment in which the child lives. Furthermore, education for children based on the concept of Islam must be maximally applied by all educators, both parents and education at schools so that the implementation of education in accordance with the concept of children's education that has been taught in the Al Quran can help make the child's personality become good. Both in terms of character, ethics, and servitude to Allah SWT. This research is a qualitative literature research. The method used is the library research method. by using the documentation method as data collection analysis, and using inductive analysis in data analysis techniques. The main source in this research is Al-Quran and relevant books and the data analysis technique of this research is using hemeneutic descriptive analysis technique. Based on the results of research data analysis, it can be concluded that the concept of education in Islam that must be implemented from the beginning to children is education about monotheism, Aqidah, education to do good to parents, education of divine values, education to perform prayers and education of politeness or ethics.